Implementasi Kebijakan Pelatihan Kerja Berbasis Kompentensi dalam Mengurangi Pengangguran di Provinsi Banten - Gian Sumarna; Jumanah; Siti Sari Nurul Isnaeni; Nurul Sa’diah; Moh. Najwan Nur (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
This study examines the implementation of competency-based job training policy as an instrument for reducing unemployment in Banten Province. The study employed a qualitative descriptive approach using secondary data from Statistics Indonesia, government regulations, official reports, scholarly publications, and relevant labour-market literature. Policy implementation was analysed using the Context, Input, Process, and Product evaluation framework, with emphasis on programme relevance, institutional capacity, resource availability, implementation processes, and expected employment outcomes. The findings indicate that competency-based job training has a strategic role in improving workforce capability by developing skills that correspond to labour-market and industrial needs. The implementation of the policy is supported by the availability of training institutions, funding allocation, certified instructors, competency-based curricula, training facilities, and collaboration between government agencies and business and industrial sectors. Nevertheless, the programme faces several constraints, including unequal access to training, limited digital literacy among prospective participants, uneven quality of facilities, insufficient industry involvement, and monitoring and evaluation mechanisms that have not fully measured post-training employment outcomes. These conditions may reduce programme effectiveness in connecting graduates with employment opportunities. The study concludes that competency-based job training requires stronger institutional coordination, demand-driven curriculum development, improved instructor and facility quality, integrated labour-market information, and expanded industry partnerships. These measures are necessary to improve programme relevance, strengthen workforce competitiveness, and support more sustainable unemployment reduction in Banten Province.